Arabinogalactan Proteins as Interactors along the Crosstalk between the Pollen Tube and the Female Tissues - Pereira, Ana M.; Lopes, Ana L.; Coimbra, Sílvia (Frontiers in Plant Science, 2016)
Arabinogalactan Proteins (AGPs) have long been considered to be implicated in several steps of the reproductive process of flowering plants. Pollen tube growth along the pistil tissues requires a multiplicity of signalling pathways to be activated and turned off precisely, at crucial timepoints, to guarantee successful fertilization and seed production. In the recent years, an outstanding effort has been made by the plant reproduction scientific community in order to better understand this process. This resulted in the discovery of a fairly substantial number of new players essential for reproduction, as well as their modes of action and interactions. Besides all the indications of AGPs involvement in reproduction, there were no convincing evidences about it. Recently, several studies came out to prove what had long been suggested about this complex family of glycoproteins. AGPs consist of a large family of hydroxyproline-rich proteins, predicted to be anchored to the plasma membrane and extremely rich in sugars. These two last characteristics always made them perfect candidates to be involved in signalling mechanisms, in several plant developmental processes. New findings finally relate AGPs to concrete functions in plant reproduction. In this review, it is intended not only to describe how different molecules and signalling pathways are functioning to achieve fertilization, but also to integrate the recent discoveries about AGPs along this process.